Validation of the cough phenotype TBQ among elderly Finnish subjects. Issue 4 (24th October 2022) - Koskela, Heikki O.; Kaulamo, Johanna T.; Selander, Tuomas A.; Lätti, Anne M.
Background: Phenotypes can be utilised in the clinical management of disorders. Approaches to phenotype disorders have evolved from subjective expert opinion to data-driven methodologies. A previous cluster analysis among working-age subjects with cough revealed a phenotype TBQ (triggers, background disorders, quality-of-life impairment), which included 38% of the subjects with cough. The present study was carried out to validate this phenotyping among elderly, retired subjects with cough. Methods: This was an observational cross-sectional study conducted via email among the members of the Finnish Pensioners' Federation (n=26 205, 23.6% responded). The analysis included 1109 subjects with current cough (mean±sd age 72.9±5.3 years; 67.7% female). All filled in a comprehensive 86-item questionnaire including the Leicester Cough Questionnaire. Phenotypes were identified utilising k-means partitional clustering. Results: Two clusters were identified. Cluster A included 75.2% of the subjects and cluster B 24.8% of the subjects. The three most important variables to separate the clusters were the number of cough triggers (mean±sd 2.47±2.34 versus 7.08±3.16, respectively; p<0.001), Leicester Cough Questionnaire physical domain (5.38±0.68 versus 4.21±0.81, respectively; p<0.001) and the number of cough background disorders (0.82±0.78 versus 1.99±0.89 respectively; p<0.001). Conclusion: The phenotype TBQ could be identified also among elderly, retired subjects with cough, thus validating the previous phenotyping among working-age subjects. The main underlying pathophysiological feature separating the phenotype TBQ from the common cough phenotype is probably hypersensitivity of the cough reflex arc. The previously described cough phenotype TBQ (triggers, background disorders, quality-of-life impairment) and the common cough phenotype can be identified in elderly, retired subjects with current cough https://bit.ly/3cygezO